Effectiveness of solution-focused group counseling to improve planned happenstance skills of student - M Arli Rusandi; Dwi Yuwono Puji Sugiharto; Sunawan Sunawan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This study aimed to determine the effectiveness of solution-focused group counseling to improve students planned happenstance skills. The experimental research method way repeated measures with pretest design and multiple posttest design, involving 5 students as participants which from 24 upperclassman of the guidance and counseling FKIP ULM which have low planned happenstance skills. The result of the research by using one-way ANOVA for repeated measures test showed that solution-focused group counseling was effective in improving the planned happenstance skills (F (2,8) = 325,895; p<0,001).